Kelayakan Media Pembelajaran Mind Mapping untuk Keterampilan Berbicara Bahasa Jerman Level A1 - Rahmat, Aceng; Barnabas, Raden Ahmad; Purwanto, Anim; Anisah, Lina (Universitas Pattimura, 2025)
This study aims to develop and evaluate the feasibility of a mind mapping-based learning media to enhance speaking skills in German at the A1 level. The research employed a Research and Development (R&D) approach using the 4D model, although it was implemented only up to the Develop stage. The results showed that during the define stage through curriculum analysis, student characteristics, and interviews with lecturers found that students struggled to organize ideas, had limited vocabulary, and lacked confidence when speaking. In the Design stage, the researcher developed a mind map with a visual structure and vocabulary aligned with the theme Tagesablauf. The validation results indicated that the media was highly feasible, with a score of 92% from the content expert and 88% from the media expert. A limited trial involving 25 students yielded positive responses, with an average score of 90.8%, indicating that the media is highly feasible for use. The mind mapping media proved to be not only technically viable but also pedagogically effective, making it a suitable alternative for teaching beginner-level German speaking skills.